Cholesterol Crystal Embolism and Chronic Kidney Disease - Li, Xuezhu (Int J Mol Sci, 2017)
Renal disease caused by cholesterol crystal embolism (CCE) occurs when cholesterol crystals become lodged in small renal arteries after small pieces of atheromatous plaques break off from the aorta or renal arteries and shower the downstream vascular bed. CCE is a multisystemic disease but kidneys are particularly vulnerable to atheroembolic disease, which can cause an acute, subacute, or chronic decline in renal function. This life-threatening disease may be underdiagnosed and overlooked as a cause of chronic kidney disease (CKD) among patients with advanced atherosclerosis. CCE can result from vascular surgery, angiography, or administration of anticoagulants. Atheroembolic renal disease has various clinical features that resemble those found in other kidney disorders and systemic diseases. It is commonly misdiagnosed in clinic, but confirmed by characteristic renal biopsy findings. Therapeutic options are limited, and prognosis is considered to be poor. Expanding knowledge of atheroembolic renal disease due to CCE opens perspectives for recognition, diagnosis, and treatment of this cause of progressive renal insufficiency.